2017
DOI: 10.1111/jav.01292
|View full text |Cite
|
Sign up to set email alerts
|

Individual consistency of long‐distance migration in a songbird: significant repeatability of autumn route, stopovers and wintering sites but not in timing of migration

Abstract: Through new tracking techniques, data on timing and routes of migration in long‐distance migrant birds are accumulating. However, studies of the consistency of migration of the same individuals between years are still rare in small‐sized passerine birds. This type of information is important to understand decisions and migration abilities at the individual level, but also for life history theory, for understanding carry over effects between different annual cycle stages and for conservation. We analysed indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 66 publications
2
57
0
Order By: Relevance
“…The travel segments were three segments in Europe and Africa for the red-backed shrike and two segments for the great reed warbler (Table 1, Fig. 1; the birds' regional locations were broadly estimated from the autumn migratory routes as demonstrated by earlier geolocator studies in Tøttrup et al 2012, Lemke et al 2013, Hasselquist et al 2017. Both birds completed all travel segments in high pressure conditions and the comparison showed that the SA heights were underestimated for the times and regions of the two individuals in this study.…”
Section: Data Treatment and Analysessupporting
confidence: 52%
See 3 more Smart Citations
“…The travel segments were three segments in Europe and Africa for the red-backed shrike and two segments for the great reed warbler (Table 1, Fig. 1; the birds' regional locations were broadly estimated from the autumn migratory routes as demonstrated by earlier geolocator studies in Tøttrup et al 2012, Lemke et al 2013, Hasselquist et al 2017. Both birds completed all travel segments in high pressure conditions and the comparison showed that the SA heights were underestimated for the times and regions of the two individuals in this study.…”
Section: Data Treatment and Analysessupporting
confidence: 52%
“…In this study we did not use these data since some light level recordings either had failed or were of poor quality. When approximating regions for comparison of standard atmosphere estimates and geopotential heights of altitudes, and when describing the flight segments of the birds, we used earlier published spatiotemporal patterns from individuals of the same populations of red-backed shrikes (Tøttrup et al 2012) and great reed warblers (Lemke et al 2013, Hasselquist et al 2017.…”
Section: Data Loggersmentioning
confidence: 99%
See 2 more Smart Citations
“…We used empirical data on 141 adult males, 131 adult females, and 287 chicks from our long term study population of great reed warblers breeding at lake Kvismaren (59°10'N, 15°25'E) in southern Central Sweden Hasselquist, Montras-Janer, Tarka, & Hansson, 2017;Roved et al, 2018). The adult individuals in our data set have been observed, examined, and ringed in the period 1984-2004, and the chicks constitute the 1998 and 1999 cohorts from the same population, with addition of one nest from each of the years 1992 and 1996 (cf.…”
Section: Data Setmentioning
confidence: 99%